Meningkatkan Kompetensi Profesionalisme Guru Melalui Supervisi Akademik di SD 14 Belanti Barat - Widya Yati; Hadiyanto Hadiyanto (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
This study aims to find out how academic supervision by school principals which can improve teacher professional competence in public. This research used an action research approach with descriptive method. Data collection techniques using interviews, observation, and documentation study. The subjects of the study were elementary school teachers at SDN 14 Belanti Barat Padang. Data were analyzed using reduction, presentation, and conclusion drawing techniques. Based on the research result, it can be concluded that the academic supervision of school principals can improve the professional competence of teachers at SDN 14 Belanti Barat. This can be seen from the achievement of the average value before and after being given guidance as it has increased in the first cycle the average value is 71.8 and in the second cycle is 78.64.